Peningkatan Komunikasi Risiko (Risk Communication) Bencana Kebakaran di Gang Segara RT. 29 Kelurahan Klandasan Ilir Kota Balikpapan - Pratomo, Rahmat Aris; Jauhari, Mohammad Rif’at; Abimanyu, Abimanyu; Permata Harry, Early Putra; Muhding, Noor Zaqiyah; Hartasi, Nur Sri; Sukmawati, A. Atifa; Annisa, Zahratu; Mustofa, Umar; Ghozali, Achmad; Purwanto, Muhammad Qoirul (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
The characteristics of the neighbourhood of Gang Segara RT. 29 Kelurahan Klandasan Ilir, which consists of high building density, irregular building patterns, low building quality, and lack of firefighting facilities, indicates a high fire risk in this area. This community service programme is conducted to improve risk communication as one of the efforts to reduce the impact of disaster. The method used was facilitating the entire representative of each household on fire disaster risk. This activity began with identifying the level of risk of fire disaster, followed by an assessment of mitigation priorities and assistance in socialising improved risk communication. The findings show that the majority of areas are high risk and there are 4 priority mitigation efforts that need to be improved as an effort to improve fire disaster risk reduction. These efforts are the procurement of fire extinguishers, distribution of fire disaster sign systems and assembly points, provision of evacuation routes, and socialisation of fire disaster training.